DAMPAK NEGATIF ADIKSI PENGGUNAAN SMARTPHONE TERHADAP ASPEK-ASPEK AKADEMIK PERSONAL REMAJA - Annisa Nurul Utami (Perspektif Ilmu Pendidikan, 2019)
Technology development in today’s digital era expands the scope of electronic media, such as smartphone, to be more easily accessed by adolescents. A smartphone has indeed the main functions generally as a means of communication in distance barriers, and a means of information gathering through the Internet. In spite of this, the prevalence of smartphones among adolescents affects not merely in beneficial way to their academic experiences quality, but also could potentially give negative impacts. Therefore, this systemathic review collects the findings of both relevant quantitive and qualitative studies regarding the negative impacts of smartphone addiction on adolescent’s personal academic aspects. Selected studies were identified from two databases to be presented in qualitative metasummary. We selected 10 studies based on the selection criteria. From the assessment, results found that smartphone addiction among senior and junior high school students could raise some risks as follows: lower academic achievements, decreased academic engagement, increased academic institution disaffection, higher tendency of anxiety, and deeper depression symptoms. Other problematic behaviors that were observed in one of selected studies were: thought problems, attention problems, antisocial-action-related aggressiveness, difficulties in building positive self-identity, and greater problems relating to self-destruction. The most frequently discovered personal academic aspect as a negative impact mentioned by participants was the decrease of academic achievement. This consideration about negative impacts of smartphone addiction on personal academic aspects offers information for parents, teachers, and the professionals to construct the anticipations of academic-related disadvantages for adolescents (e.g., an educative socialization program about utilizing smartphone wisely).